1998
DOI: 10.1021/la980724c
|View full text |Cite
|
Sign up to set email alerts
|

Air Oxidation of Self-Assembled Monolayers on Polycrystalline Gold:  The Role of the Gold Substrate

Abstract: Alkanethiolates in self-assembled monolayers on gold oxidize in air, in the dark, to form sulfinates and sulfonates. The kinetics of oxidation, however, vary depending on the morphology of the underlying gold, with the rate of oxidation increasing dramatically with a decrease in the size of the grains and the amount of Au(111) on the surface. This difference in kinetics of oxidation is sufficiently great that it may provide insight into discrepancies among previous reports in the literature regarding the inert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
157
2
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(169 citation statements)
references
References 19 publications
9
157
2
1
Order By: Relevance
“…The inherent well-packed nature of such SAMs enables the formation of a non-interdigitated hybrid lipid bilayer comprising a layer of phospholipids on top of a layer of surface bound SAM alkyl chain molecules. 14,17 However, several inherent drawbacks limit their more widespread use, which include moisture sensitivity of silanes, 18,19,20 the instability of thiols towards oxidation, 21 the requirement for specific substrate surfaces for self-assembly (such as silicon, 22 glass, 23 gold, 24 platinum, 25 or palladium 26 ), and the lack of readily available high surface area 3-dimensional variants.…”
Section: Introductionmentioning
confidence: 99%
“…The inherent well-packed nature of such SAMs enables the formation of a non-interdigitated hybrid lipid bilayer comprising a layer of phospholipids on top of a layer of surface bound SAM alkyl chain molecules. 14,17 However, several inherent drawbacks limit their more widespread use, which include moisture sensitivity of silanes, 18,19,20 the instability of thiols towards oxidation, 21 the requirement for specific substrate surfaces for self-assembly (such as silicon, 22 glass, 23 gold, 24 platinum, 25 or palladium 26 ), and the lack of readily available high surface area 3-dimensional variants.…”
Section: Introductionmentioning
confidence: 99%
“…They found that alkanethiolate SAMs on surfaces with higher area densities of grain boundaries oxidized within hours to days to the corresponding sulfinates and sulfonates, whereas those having lower area densities showed no apparent oxidation after two weeks. [6] There are a number of methods for the preparation of thin gold films, and the quality of the resulting gold surface depends on, for example, the annealing conditions, evaporation rates, and substrate types. [7] When mica substrates are used, ultraflat gold and silver surfaces comprising welldefined h111i-oriented crystals can be grown.…”
mentioning
confidence: 99%
“…We can observe the same Au, S, Fe and N signals again, and also a small amount of oxidized S species (binding energies > 165 eV) produced during the prolonged exposure of www.chemphyschem.org the sample to oxygen and light. [15] It should be recalled that no traces of Fe and N are observed when performing the same procedure with a clean HOPG in contact with AuNP-free melanin solutions. These results demonstrate that the melanin-iron modified NT-AuNPs are delivered to the NaOH solution by a simple change in the applied potential and they are then recovered in hexane solution by extraction.…”
Section: Resultsmentioning
confidence: 96%